Protecting lithium metal anodes in lithium–sulfur batteries: A review - Bi, Chen-Xi; Hou, Li-Peng; Li, Zheng; Zhao, Meng; Zhang, Xue-Qiang; Li, Bo-Quan; Zhang, Qiang; Huang, Jia-Qi (Energy material advances, 2023)
Lithium–sulfur (Li–S) batteries are considered as one of the most promising next-generation energy storage devices because of their ultrahigh theoretical energy density beyond lithium-ion batteries. The cycling stability of Li metal anode largely determines the prospect of practical applications of Li–S batteries. This review systematically summarizes the current advances of Li anode protection in Li–S batteries regarding both fundamental understanding and regulation methodology. First, the main challenges of Li metal anode instability are introduced with emphasis on the influence from lithium polysulfides. Then, a timeline with 4 stages is presented to afford an overview of the developing history of this field. Following that, 3 Li anode protection strategies are discussed in detail in aspects of guiding uniform Li plating/stripping, reducing polysulfide concentration in anolyte, and reducing polysulfide reaction activity with Li metal. Finally, 3 viewpoints are proposed to inspire future research and development of advanced Li metal anode for practical Li–S batteries.